The hot zone [large type] - Castle, Jayne (Castle, Jayne. Rainshadow novel., 2014)
Sparks erupt when Sedona Snow, who manages a small hotel and tavern on Rainshadow Island with her faithful sidekick, Lyle, and who is trying to put her tragic past behind her, catches the attention of a new Guild boss in town.